Pengembangan Produk Olahan Rumput Laut bagi Peningkatan Pengetahuan dan Keterampilan Komunitas Mitra Baji Pamai - Kasmiati; Citra Malina, Asmi; Nasrum Massi, Muh.; Rahmi, Rahmi (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia, 2025)
Seaweed is one of the most abundant coastal resources in Baji Pamai, yet the community has long depended on selling it in dried form, resulting in limited economic benefits. This community service program aimed to improve the knowledge and skills of coastal families in processing seaweed into a high-value food product, specifically seaweed-based cendol. The activity was designed to strengthen the community’s capacity in diversifying seaweed utilization and to support the development of a sustainable household-scale product. The program consisted of several stages: preparation, counseling, training, practice, and mentoring. Twenty participants were involved, selected based on their involvement in seaweed production and willingness to participate in all sessions. Counseling was conducted to enhance understanding of seaweed nutrition, product potential, and hygiene principles. This was followed by hands-on training on the entire production process, including material preparation, gel extraction, dough mixing, cendol molding, and packaging. Mentoring was provided continuously until participants demonstrated the ability to produce the product independently. The results showed a significant improvement in participants’ knowledge, with average scores increasing from 42 percent in the initial assessment to 98 percent after the counseling session. All twenty participants successfully produced seaweed cendol with acceptable texture and taste. Economically, the group was able to process three kilograms of dried seaweed worth ninety thousand rupiah into two hundred and fifty bottles of seaweed cendol, generating a total revenue of two million five hundred thousand rupiah. The provision of equipment and starter materials further supported the sustainability of the initiative. This program demonstrates that simple processing technology can create substantial added value and empower coastal communities. The involvement of community members at every stage reflects the effectiveness of participatory-based training in building independence and strengthening the local economy.